Do Intellectually Gifted Children Show Similar Physical Habits, Physical Fitness Levels and Self-Perceived Body Image Than Typically Developed Children? - Aroa Otero Rodríguez; Miguel Adriano Sánchez-Lastra; José Carlos Diz; Carlos Ayán (MDPI AG, 2022)
Scientific evidence regarding whether intellectually gifted children show similar physical activity habits and physical fitness levels in comparison to typically developed children, is inconclusive. This is in part due to the scant research that has directly compared both groups of people. In this study, physical activity prevalence, self-perceived and objectively assessed physical fitness levels, and body image were assessed in a sample of 74 intellectually gifted children (mean age 11.6 ± 1.2 years). Seventy-four non-gifted children matched by age and sex were selected as a comparison cohort. Results indicated that both groups showed similar self-perceived and objectively assessed fitness levels. Physical activity habits were also similar, although significant differences were observed indicating that intellectually gifted girls were less active in comparison with non-gifted girls. Both cohorts perceived their body image accurately, although intellectually gifted children were much more satisfied with their physical appearance.